Developing Herbal Medicine, The Role of Î²-1,3/1,6-D-Glucan Forms of Polysaccharide Peptide (PsP) from Mycelia Ganoderma lucidum Extracts for Lowering Elevated Total Cholesterol Level in Patients with Heart Failure in Ischaemic Heart Disease - Sargowo, Djanggan; Wihastuti, Titin Andri; Dewi, Elvira Sari; Saputri, Diana Nanda (JSMARTech, 2020)
High levels of total cholesterol can worsen the condition of ischemic heart failure. Polysaccharide peptide (PsP) is a capsule of Ganoderma lucidum extract. This study aims to measure changes in total cholesterol levels in patients with ischemic heart failure before and after the administration of PSP and Placebo and to analyze differences in decreases in total cholesterol levels between PSP and Placebo group. This research is a true experiment with a prospective double-blind randomized control method through pre-post test design. The sample consisted of 26 patients, divided into 2 groups and given PSP or placebo capsules per oral interventions carried out every day for 90 days. Venipuncture blood was taken before and after the intervention to measure total cholesterol levels by spectrophotometry methods. Paired T Test was used to determine the average reduction in total cholesterol levels for each group. Independent T Test was used to determine the difference of reduction in total cholesterol average between the two groups. The decrease of total cholesterol average level in PsP group was 24.3 mg/dl (p value 0.001) and an increase of Placebo group was 8.3 mg/dl (p value 0.099). Comparison of the average reduction in total cholesterol levels in PsP : Placebo group was 24.31: -8.31 mg/dl (p value 0.000). There was significant decrease total cholesterol levels in PsP group and neither was of the Placebo group. In addition, there was significant difference in the reduction of total cholesterol levels between PSP and Placebo group.